EVCNA 2021
DOI: 10.20517/evcna.2020.07
|View full text |Cite
|
Sign up to set email alerts
|

Defining the landscape of circRNAs in non-small cell lung cancer and their potential as liquid biopsy biomarkers: a complete review including current methods

Abstract: Despite the significant decrease in population-level mortality of lung cancer patients as reflected in the Surveillance Epidemiology and End Results program national database, lung cancer, with non-small cell lung cancer (NSCLC) in the lead, continues to be the most commonly diagnosed cancer and foremost cause of cancer-related death worldwide, primarily due to late-stage diagnosis and ineffective treatment regimens. Although innovative single therapies and their combinations are constantly being tested in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…CircRNAs are highly enriched in EVs [ 7 ] and show a relatively high stability compared to other forms of RNA [ 8 ]. Several studies have highlighted their potential as liquid biopsy biomarkers [ 12 ] but current limitations in circRNA quantification methods are limiting their implementation in the clinical setting. Consequently, new, and robust protocols for circRNA analysis are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are highly enriched in EVs [ 7 ] and show a relatively high stability compared to other forms of RNA [ 8 ]. Several studies have highlighted their potential as liquid biopsy biomarkers [ 12 ] but current limitations in circRNA quantification methods are limiting their implementation in the clinical setting. Consequently, new, and robust protocols for circRNA analysis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that aberrant expression of certain circRNAs can promote cancer development and progression [ 11 ]. Additionally, some circRNAs have been investigated as liquid biopsy biomarkers for the early detection of lung cancer and other solid tumors [ 12 , 13 ]. However, the lack of consensus on a robust and standardized protocol for circRNA quantification is holding back the development of clinically applicable assays.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vescicles are also a source of more abundant genetic information when compared with ctDNA and they are characterised by high stability, even though DNA extraction procedures are technically more complex. Finally, microRNA are small non-coding RNA, frequently deregulated in tumours and they can be detected and analysed in plasma, even though several technical issues have to be faced before validation for clinical practice [ 168 – 170 ].…”
Section: The Day After Tomorrow: What We Are Looking Formentioning
confidence: 99%
“…circRNAs are a newly re‐defined type of endogenous RNA molecules originated by a noncanonical process called ‘back‐splicing’. Through this mechanism, the 5′ splice donor covalently links to the 3′ end of an upstream exon, resulting in a single‐stranded circular structure which can include one or different exonic/intronic regions [ 1 ]. This particular assembly lacking a poly(A) tail makes them very stable and resistant to exonuclease‐mediated degradation when compared to their linear counterparts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…RT‐qPCR is widely used as a quantification tool for circRNA expression studies. While its sensitivity and short turnaround time proves beneficial for circRNA research, several events such as template switching, rolling circle amplification, or the bias attached to this technique may hinder the results [ 13 ]. In addition, it does not allow high‐throughput analysis, which is necessary for biomarker discovery.…”
Section: Introductionmentioning
confidence: 99%